The multimedia service session handoff method in heterogeneous wireless networks. (2nd March 2012) - Shen, Yulong; Pei, Qingqi; Xu, Qijian; Zhang, Zhiwei
The IP Multimedia Subsystem (IMS) can provide multimedia services between heterogeneous wireless networks. But the efficiency of the service session handoff will bring a significant impact to user experience. For the integration of heterogeneous wireless networks, we propose a Session Initiation Protocol (SIP) based multimedia service session handoff method named MS 2 HM. To reduce the handoff delay between heterogeneous wireless networks, the MS 2 HM uses the methods of advance registration and old-new address temporary matching. We modelled the node processing delay and network transmission delay, and analyse the total delay and the packet loss rate of the MS 2 HM. Specially, this paper contrastively analyses the handoff delay under different frame error control in the 3G-WLAN integrated network, and the result shows that MS 2 HM has lower handoff delay than the method proposed by Wedlund and Schulzrinne. The MS 2 HM can meet the low delay and low packet loss rate requirements of IMS service session handoff between heterogeneous wireless networks, and ensure the QoS of the IMS services.